P103 Degradation and formation of type III, IV and V collagen are associated with disease activity, disease severity and disease extension in patients with ulcerative colitis. (25th January 2019) - Mortensen, J H; Domislovic, V; Karsdal, M A; Brinar, M; Krznaric, Z; Manon-Jensen, T
Abstract: Background: Ulcerative colitis (UC) is an idiopathic chronic inflammatory bowel disease, where increased matrix metalloproteinases are the major contributor to the intestinal tissue remodelling UC. The intestinal basement membrane (main constituent is type IV collagen) is directly positioned underneath the epithelial cells. The supportive interstitial matrix (main constituent are type I, III and V collagens) is mainly produced by fibroblasts. Both matrices are important for intestinal health and are highly affected in UC. We investigated serum biomarkers of collagen degradation and formation of the respective extracellular matrix (ECM) compartments and their association with disease activity, severity and extension in UC. Methods: In total, 29 UC patients and 29 healthy donors (HD) were included. A combination of the partial mayo score and biochemical activity was used to determine disease activity ( p Mayo > 1 and CRP >5). Disease severity and extension was assessed by Montreal classification. Biomarkers of type III collagen degradation (C3M) and formation (PRO-C3), type IV collagen degradation (C4M) and formation (PRO-C4), type V collagen formation (PRO-C5) and C-reactive protein (CRP) were measured in serum by ELISA. One-way ANOVA (Tukey's multiple comparisons test), and spearman rho correlations were applied for statistical analyses. Results: C4M was significantly elevated in active UC compared with UC in remission ( p < 0.05) and HD ( p < 0.001), and PRO-C4 was also significantly elevated in active UC compared with UC in remission ( p < 0.01) and HD ( p < 0.001). C3M was significantly elevated in active UC compared with UC in remission ( p < 0.05) and HD ( p < 0.05), whereas PRO-C3 was significantly elevated in active UC and UC in remission compared with HD ( p < 0.001). PRO-C5 was elevated in active UC compared with HD ( p < 0.01). In addition, C3M ( r = 56, p < 0.01), C4M ( r = 0.41, p < 0.05), PRO-C4 ( r = 58, p < 0.001), PRO-C5 ( r = 49, p < 0.01), and CRP ( r = 47, p < 0.01) correlated with disease severity, and PRO-C4 ( r = 48, p < 0.01), PRO-C5 ( r = 0.38, p < 0.05), and CRP ( r = 45, p < 0.01) correlated with disease extension. Conclusions: The biomarkers C3M and C4M were associated with disease activity in UC and disease severity in addition to PRO-C4 and PRO-C5. PRO-C4 and PRO-C5 also correlated with disease extension. These data demonstrated that ECM remodelling of the intestinal basement membrane and interstitial matrix are associated with disease status and progression, which can be used to optimise treatment strategies for UC patients.